Fluvial activity of the late-glacial to Holocene “Bergstraßenneckar” in the Upper Rhine Graben near Heidelberg, Germany - first results - Engel, Max; Henselowsky, Felix; Roth, Fabian; Kadereit, Annette; Herzog, Manuel; Hecht, Stefan; Lindauer, Susanne; Bubenzer, Olaf; Schukraft, Gerd (Quaternary science journal, 2022)
The term “Bergstraßenneckar” (BSN) refers to an abandoned course of the river Neckar. It flowed in a northern direction east of the river Rhine in the eastern part of the northern Upper Rhine Graben in southwestern Germany. The former meandering course merged with the Rhine ca. 50 km further north of the site of the present-day confluence near Mannheim. The palaeo-channels are still traceable by their depressional topography, in satellite images and by the curved boundaries of adjacent settlements and land parcels. In the plan view, satellite and aerial images reveal a succession of meander bends, with older bends being cut off from younger channels. Based on stratigraphic investigations of the channel infill in the northern part of the BSN, fluvial activity is assumed from ca. 14 500 years ago until the onset of the Holocene. We present results of the first stratigraphic investigations at two sites in the southern part of the BSN near Heidelberg (Rindlache, Schäffertwiesen), together with results from granulometric, carbonate and organic content analyses, as well as electrical resistivity tomography (ERT) measurements. The data clearly show a change from high-energy fluvial bedload (sand, gravel) to low-energy fluvio-limnic suspended load (organoclastic and calcareous mud) and to peat formation. Radiocarbon dating indicates a time lag of ca. 1500 years between the cut-off meander site (Schäffertwiesen) and the younger site (Rindlache) that was possibly still active until the present-day confluence near Mannheim was established and the BSN eventually became abandoned. Our preliminary data conform with the pedo-sedimentary evidence from the northern BSN, but slight differences in the stratigraphic pattern of the youngest channels are identified: whilst for the younger channel sections of the northern BSN the channel-bottom facies (sand, gravel) is directly overlain by peat, the channel at Rindlache shows substantial intervening mud deposition, which is interpreted as suspension load from flooding by the new Neckar channel nearby. The study shows that more chronostratigraphic data from channel sections of the southern BSN are needed to better constrain the timing of the fluvial activity and to decipher the reasons for the abandonment of the BSN. These data are also necessary to better understand the pattern of temporary reactivation of the BSN channels across the Holocene and their usage by humans, which can be deduced from historical sources and archaeological data.
Gesehen am 30.03.2023
Keywords: Oberrheinisches Tiefland; Neckar; Rhein-Neckar-Gebiet